Improving Prediction of Amyloid Deposition in Mild Cognitive Impairment With a Timed Motor Task. (22nd September 2022) - Schaefer, Sydney Y.; Duff, Kevin; Hooyman, Andrew; Hoffman, John M.
Cortical amyloid deposition is one of the hallmark biomarkers of Alzheimer's disease (AD). However, given how cost- and time-intensive amyloid imaging can be, there is a continued need for a low-cost, non-invasive, and accessible enrichment strategy to pre-screen individuals for their likelihood of amyloid prior to imaging. Previous work supports the use of coordinated limb movement as a potential screening tool, even after controlling for cognitive and daily function. Thirty-six patients diagnosed with amnestic mild cognitive impairment over the age of 65 underwent 18F-Flutemetamol amyloid-positron emission tomography (PET) imaging and then completed a timed motor task involving upper limb coordination. This task takes ∼5 minutes to administer and score. Multivariate linear regression and receiver operator characteristic analyses showed that including motor task performance improved model prediction of amyloid burden. Results support the rationale for including functional upper extremity motor assessment as a cost- and time-effective means to screen participants for amyloid deposition.